Economic Development Through Aid or International Trade - Ana Mihei (CES Working Papers, 2010)
Economic development is the supreme goal of modern civilization. This phenomenon is seen not just in terms of growth, but rather as an overall improvement in living standards. Economic development is a national goal, but also an objective of international economic bodies. Talks about development are held in the context of the opposition between developed countries and developing countries.In this article, we discuss whether development aid that originates from industrialized states supports sustainable economic rise of the countries lagging behind and whether it is preferable to let market operate freely, through the liberalization of international trade. Our conclusion is that economic development through the promotion of free trade would be achieved faster and more efficiently, based on net gains from trade and the pride of the peoples who would have won by themselves their daily bread and a place in the global market.
Keywords: 330; economic development; governmental financial aid; international trade